Застосування нейронних мереж для задач захисту інформації - Андреас, Д. В. (ХНУРЕ, 2025)
Modern information systems are increasingly becoming targets of cyber threats, among which DDoS attacks are of particular danger. In recent years, the number of such attacks has increased significantly, and their complexity and effectiveness have increased due to the use of botnets, automated scripts and masking algorithms.
Keywords: захист інформації; DDoS attack